2017
DOI: 10.15252/emmm.201707502
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine receptor CX 3 CR 1 coordinates monocyte recruitment and endothelial regeneration after arterial injury

Abstract: Regeneration of arterial endothelium after injury is critical for the maintenance of normal blood flow, cell trafficking, and vascular function. Using mouse models of carotid injury, we show that the transition from a static to a dynamic phase of endothelial regeneration is marked by a strong increase in endothelial proliferation, which is accompanied by induction of the chemokine CX 3 CL1 in endothelial cells near the wound edge, leading to progressive recruitment of Ly6Clo monocytes expressing high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…An early reduction in intermediate monocytes may be followed by expansion of cells bearing intermediate cell markers from the classical pool as we have described in the current study, albeit these cells that were grown in culture for 24 h appear to be functionally altered. In these cells, we showed reduced expression of TLR4 and TLR5 that are involved in sensing pathogen- and damage-associated molecular patterns as well as reduction in CX 3 CR1 that is involved in monocyte adhesion, survival, and recruitment (45, 46), CCR2 that mediates chemotaxis toward bacteria and necrotic cells, CD36, a receptor involved in scavenging debris and a reduction in the co-stimulatory molecule CD86 that mediates lymphocyte activation. Upregulation of IL-10 is further evidence of an immunosuppressive phenotype, and importantly also shows that this is an active process, or reflective of a physiological process of immune shut-down, rather than functional anergy.…”
Section: Discussionmentioning
confidence: 97%
“…An early reduction in intermediate monocytes may be followed by expansion of cells bearing intermediate cell markers from the classical pool as we have described in the current study, albeit these cells that were grown in culture for 24 h appear to be functionally altered. In these cells, we showed reduced expression of TLR4 and TLR5 that are involved in sensing pathogen- and damage-associated molecular patterns as well as reduction in CX 3 CR1 that is involved in monocyte adhesion, survival, and recruitment (45, 46), CCR2 that mediates chemotaxis toward bacteria and necrotic cells, CD36, a receptor involved in scavenging debris and a reduction in the co-stimulatory molecule CD86 that mediates lymphocyte activation. Upregulation of IL-10 is further evidence of an immunosuppressive phenotype, and importantly also shows that this is an active process, or reflective of a physiological process of immune shut-down, rather than functional anergy.…”
Section: Discussionmentioning
confidence: 97%
“…In mice, these are called Ly6C lo monocytes and express CD43, CD11c and the transcription factors Nr4a1 , Pou2f2 ( Gamrekelashvili et al, 2016 ; Patel et al, 2017 ; Varol et al, 2007 ; Yona et al, 2013 ). These monocytes have a long lifespan and remain mostly within blood vessels, where they crawl along the luminal side of blood vessels to monitor endothelial integrity and to orchestrate endothelial repair ( Auffray et al, 2007 ; Carlin et al, 2013 ; Getzin et al, 2018 ). Steady-state monocyte conversion occurs in specialized endothelial niches and is regulated by monocyte Notch2 signaling activated by endothelial Notch ligands ( Avraham-Davidi et al, 2013 ; Bianchini et al, 2019 ; Gamrekelashvili et al, 2016 ; Varol et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the three subsets of monocytes circulate in dynamic equilibrium, with 99% of classical monocytes leaving the circulation and the remaining 1% becoming intermediate monocytes, 100% of which then mature in the circulation to become non-classical monocytes under steady state conditions [14]. Moreover, non-classical monocytes have been proposed to act as custodians of vasculature by maintaining endothelial cells integrity [14,15]. Additionally, several studies have shown that circulating CD16 + monocytes are found in large numbers in patients with inflammatory processes and infectious diseases [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%